What next after basal insulin? Treatment intensification with lixisenatide in Asian patients with type 2 diabetes mellitus: 基础胰岛素之后是什么?亚洲2型糖尿病患者使用利西那肽强化治疗. (23rd January 2017) - Chan, Wing B.; Luk, Andrea; Chow, Wing S.; Yeung, Vincent T.F.
Highlights: This article addresses the unmet needs of the Asian population with type 2 diabetes. This review details the research into the use of glucagon‐like peptide‐1 (GLP‐1) receptor agonists in general, and lixisenatide in particular, in the Asian population. The review also examines the importance of treatment intensification in patients who fail to achieve glycemic control with basal insulin. Mean (±SEM) plasma glucose profiles at baseline and Week 8 following initiation of treatment with lixisenatide or liraglutide in patients receiving insulin glargine with or without metformin (modified intent‐to‐treat population). The hyperglycemia threshold is based on International Diabetes Federation 2011 guidelines. 60 Statistical tests compared treatment arms at each time point at Week 8. * P < 0.05 for lixisenatide 20 μg versus liraglutide 1.2 mg; † P < 0.05 for lixisenatide 20 μg versus liraglutide 1.8 mg; ‡ P < 0.05 for liraglutide 1.2 and 1.8 mg versus lixisenatide 20 μg; § P < 0.05 for liraglutide 1.8 mg versus lixisenatide 20 μg. The x ‐axis labels show the time after injection of the study agent; for example, T1H30 means 1 h and 30 min after injection. (Reproduced with permission of the American Diabetes Association from Meier et al. 61 ). Abstract: There is increasing evidence that the pathophysiology of type 2 diabetes mellitus (T2DM) in Asian patients differs from that in Western patients, with early phase insulin deficiencies, increased postprandial glucose excursions, and increased sensitivity to insulin. Asian patients may also experience higher rates of gastrointestinal adverse events associated with glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs), such as nausea and vomiting, compared with their Western counterparts. These factors should be taken into consideration when selecting therapy for basal insulin treatment intensification in Asian patients. However, the majority of studies to establish various agents for treatment intensification in T2DM have been conducted in predominantly Western populations, and the levels of evidence available in Chinese or Asian patients are limited. This review discusses the different mechanisms of action of short‐acting, prandial, and long‐acting GLP‐1RAs in addressing hyperglycemia, and describes the rationale and available clinical data for basal insulin in combination with the short‐acting prandial GLP‐1RA lixisenatide, with a focus on treatment of Asian patients with T2DM.